Need Analysis in Developing TBLT-Based Digital Storybook for 7th Grade Students - Pradnyawati, Kadek Rikha; Myartawan, I Putu Ngurah Wage; Pratiwi, Ni Putu Astiti (Universitas Pendidikan Ganesha, 2023)
Language teaching needs to use media and models that help student learning activities. And task-based learning is a learning model that has been widely applied in schools but does not yet have the appropriate criteria for this model in facilitating literacy activities. The role of creative and innovative learning media is also very important in increasing student motivation in literacy activities based on TBLT. This research aims to analyze the needs of students as initial stage to develop a TBLT-based digital story book to promote student literacy activities in 7th grade students. This study uses the Design & Development model by Richey & Klein as a research methodology. There are four stages in this method carried out by researchers namely, Analysis, Design, Development, and Evaluation. In collecting data, several instruments used were syllabus analysis, interview guides, observations, questionnaires, blueprints, and assessment rubrics. The results show that TBLT-based digital storybooks help teachers and students in the learning process and literacy activities as innovative media and provide motivation to be interested in literacy.